Gaya Bahasa Personifikasi dalam Novel Drupadi Karya Seno Gumira Ajidarma - Nurnani, Dewi (Institut Seni Indonesia Surakarta, 2023)
The article entitled “ Gaya Bahasa Personifikasi Dalam Novel Drupadi Karya Seno Gumira Ajidarma (Personification Language Style in the Novel Drupadi by Seno Gumira Ajidarma)” attempts to describe the personification language style that is dominantly used by the author in expressing his thoughts and ideas in the novel Drupadi. Apart from that, the influence of the personification language style on Drupadi’s story as outlined by the author in the novel is also the focus of the analysis. This research uses a qualitative descriptive method with a structural (intrinsic) approach. Data was obtained through literature study and interviews. The results of this research show that the dominant personification language style used by the author in the novel Drupadi gives a beautiful, dramatic and lively impression so that it attracts the reader’s attention and interest. Apart from that, the personification language style also helps and gives space to the reader’s imagination in capturing and understanding what the author wants to express. The readers will be able to judge or conclude that the literary work or novel is good, interesting, or impressive, and so on.